The Development of a Short Chinese Version of the State-Trait Anxiety Inventory - Du, Qingyun; Liu, Haowen; Yang, Chengjiao; Chen, Xiaoyu; Zhang, Xiaoyuan (Frontiers in Psychiatry, 2022)
Background: Few studies on anxiety in China have used Spielberger State-Trait Anxiety Inventory (STAI) due to the length of the full version, even it is useful. The goal of this study was to develop a short Chinese version of STAI and examine its reliability and validity among the Chinese general population and psychiatric patients diagnosed with anxiety. Method: A total of 1142 participants were invited for testing of the short Chinese version of the STAI, and item analysis, validity testing and internal consistency reliability analysis were performed. Subsequently, 40 participants were enrolled to assess retest reliability 1 week later. Finally, 330 participants, including 33 psychiatric patients with anxiety, were analyzed to assess the criterion and empirical validity. The Self-Rating Anxiety Scale (SAS) and Satisfaction with Life Scale (SWLS) were used as criteria, and receiver operating characteristic (ROC) analysis was conducted to evaluate the discrimination of the short version of STAI between the groups with and without anxiety disorders. Result: The short Chinese version of the STAI consists of 6 items for each subscale (STAI-S-6 and STAI-T-6). The Pearson correlation between each of the two shortened Chinese versions of the STAI and the full-length STAI were 0.970 and 0.962, the Cronbach’s α coefficients were 0.871 and 0.842, and the retest reliability values were 0.728 and 0.813 (p<0.001). Confirmatory factor analysis showed that the 2-factors model achieved an adequate model fit: for the STAI-S-6, CFI=0.986, TLI =0.974, and RMSEA = 0.075, and for the STAI-T-6, CFI=0.994, TLI = 0.988, and RMSEA = 0.052. The short Chinese version of the STAI had a significant positive correlation with the SAS score (r=0.289, 0.313; p<0.001) and a negative correlation with the SWLS score (r=-0.476, 0.554; p<0.001). A significant difference in the level of anxiety was found between participants with and without anxiety disorders. The diagnostic accuracy of STAI-S-6 and STAI-T-6 for major anxiety disorder was acceptable, with areas under the ROC curves of 0.798 and 0.745, respectively. Conclusions: The short Chinese version of the STAI demonstrates sound psychometric properties and is applicable in the evaluation of the level of anxiety in Chinese populations.